Penggunaan Media Lidi untuk Meningkatkan Hasil Belajar Matematika pada Pokok Bahasan Penjumlahan Bilangan Bulat - Fadli Ahmad; Akmal Hi. Dahlan (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to improve mathematics learning outcomes on the subject of the addition of integers by using the stick media as a means of solving problems. Therefore, this study uses classroom action research. In this study, researchers tried to collaborate with subject teachers to conduct learning according to the plan that had been made between researchers and subject teachers. The data collected in this study illustrates descriptive, which describes every material that will be collected. The results showed that the use of stick media on the subject of the addition of integers in fourth grade students of SD Inpres Wayabula could improve student learning outcomes. This can be seen from the results of tests before and using the stick media. The results showed, before using the media stick obtained 11 students or 78.57% who failed qualifications, 2 students or 14.28% who were qualified enough and 1 student or 7.14% who were qualified enough. Whereas after using media, sticks were obtained, student learning outcomes in the first cycle, there were 9 students or 64.28% who failed qualifications, 3 students or 21.42% who were less qualified, and 2 students or 14.28% who were sufficiently qualified, and no good student is also very good. In the second cycle there were 3 students or 21.42% who were very well qualified, 7 students or 50% were well qualified, 2 students or 14.28% were sufficiently qualified, 1 student or 7.14% who were less qualified, and accepted 1 student or 7.14% who are qualified fail.